2020
DOI: 10.1021/acsami.0c12250
|View full text |Cite
|
Sign up to set email alerts
|

∑3 Twin Boundaries in Gd2Ti2O7 Pyrochlore: Pathways for Oxygen Migration

Abstract: Understanding the chemistry at twin boundaries (TB) is a well-recognized challenge, which could enable the capabilities to manipulate the functional properties in complex oxides. The study of this atomic imperfection becomes even more important, as the presence of twin boundaries has been widely observed in materials, regardless of the dimensionalities, due to the complexities in growth methods. In the present study, we provide atomic-scale insights into a ∑3(111̅ ) ⟨11̅ 0⟩ twin boundary present in pyrochlore-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…GPA has also been used to map strain at La 2 Zr 2 O 7 (LZO)/YSZ (111) interfaces, highlighting the presence of misfit dislocations that may impact the accumulation of radiation damage at such features ( Kaspar et al, 2017 ). This approach has also been used to demonstrate the effect of strain at twin boundaries in Gd 2 Ti 2 O 7 , showing a local reduction of the oxygen migration barrier compared with the bulk ( Gupta et al, 2020 ).…”
Section: Structure Analysis From Real-space Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…GPA has also been used to map strain at La 2 Zr 2 O 7 (LZO)/YSZ (111) interfaces, highlighting the presence of misfit dislocations that may impact the accumulation of radiation damage at such features ( Kaspar et al, 2017 ). This approach has also been used to demonstrate the effect of strain at twin boundaries in Gd 2 Ti 2 O 7 , showing a local reduction of the oxygen migration barrier compared with the bulk ( Gupta et al, 2020 ).…”
Section: Structure Analysis From Real-space Imagingmentioning
confidence: 99%
“…Heterointerface engineering of fluorites, perovskites and pyrochlores has been shown to control local oxygen diffusivity ( Schweiger et al, 2017 ), to affect local radiation response ( Spurgeon et al, 2020 ) and to produce novel topological phases ( Gallagher et al, 2016 ; Li et al, 2021 ). Other types of extended crystalline defects, such as dislocations ( Sheth et al, 2016 ; Shafieizadeh et al, 2018 ) and grain boundaries ( Bowman et al, 2015 ; Bowman et al, 2017 ; Perriot et al, 2017 ; Gupta et al, 2020 ; Syed et al, 2020 ; Tong et al, 2020 ) have been shown to behave as fast oxygen transport pathways in some cases. Even small, localized, atomic displacements such as local changes in bonding environment (e.g., coordination), polyhedral distortions (e.g., bond length or angle), polyhedral tilting and the adoption of short-range polyhedral configurations or ‘structural motifs’ ( Shamblin et al, 2016 ; Sun et al, 2016 ) can affect functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…8 For instance, a typical pyrochlore Gd 2 Ti 2 O 7 demonstrates an insulating behavior, whereas Gd 2 Zr 2 O 7 is a good oxide-ion conductor. 9,10 Lanthanum-based pyrochlore/perovskite oxides have become one of the most investigated materials in the past 50 years. 11,12 It has been found that multiple A/B element substitutions may result in lattice distortions and structural transformations, especially the combination of A/B with different valences.…”
Section: Introductionmentioning
confidence: 99%
“…8 For instance, a typical pyrochlore Gd 2 Ti 2 O 7 demonstrates an insulating behavior, whereas Gd 2 Zr 2 O 7 is a good oxide-ion conductor. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…All these interfaces can play a dominant role in overall device performance, however as lower temperature operation is increasingly of interest, the role played by grain boundaries is receiving more scrutiny. 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Hence an understanding of grain boundary transport in polycrystalline MEIC materials, both of cations 23 and anions (oxygen ions), is becoming necessary. Understanding cation transport is relevant to segregation and degradation effects over the very long timescales necessary for operation and during high temperature processing.…”
mentioning
confidence: 99%